2012
DOI: 10.5194/acp-12-10257-2012
|View full text |Cite
|
Sign up to set email alerts
|

Chamber simulation of photooxidation of dimethyl sulfide and isoprene in the presence of NO<sub>x</sub>

Abstract: Abstract. To improve the model prediction for the formation of H2SO4 and methanesulfonic acid (MSA), aerosol-phase reactions of gaseous dimethyl sulfide (DMS) oxidation products [e.g., dimethyl sulfoxide (DMSO)] in aerosol have been included in the DMS kinetic model with the recently reported gas-phase reactions and their rate constants. To determine the rate constants of aerosol-phase reactions of both DMSO and its major gaseous products [e.g., dimethyl sulfone (DMSO2) and methanesulfinic acid (MSIA)], DMSO w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 46 publications
3
18
1
1
Order By: Relevance
“…1 were SO 2 , particulate MSA, and particulate sulfate, with 48 % of the product sulfur found in the particle phase. The measured MSA : sulfate ratio (∼ 2.5 : 1) is in broad agreement with those reported in Chen et al (2012). Minor species observed included dimethyl sulfoxide (DMSO), C 2 H 6 SO 2 (likely dimethyl sulfone, DMSO 2 ), and methane sulfinic acid (MSIA), known products from the addition channel, as well as CH 2 SO 2 (likely a thioacid, which may be formed as an OH oxidation product of HPMTF, Jernigan et al, 2022a) and CH 3 SO 6 N (likely methanesulfonyl peroxynitrate, formed from CH 3 S(O) 2 OO + NO 2 ).…”
Section: Comprehensive Measurements Of S-containing Productssupporting
confidence: 90%
“…1 were SO 2 , particulate MSA, and particulate sulfate, with 48 % of the product sulfur found in the particle phase. The measured MSA : sulfate ratio (∼ 2.5 : 1) is in broad agreement with those reported in Chen et al (2012). Minor species observed included dimethyl sulfoxide (DMSO), C 2 H 6 SO 2 (likely dimethyl sulfone, DMSO 2 ), and methane sulfinic acid (MSIA), known products from the addition channel, as well as CH 2 SO 2 (likely a thioacid, which may be formed as an OH oxidation product of HPMTF, Jernigan et al, 2022a) and CH 3 SO 6 N (likely methanesulfonyl peroxynitrate, formed from CH 3 S(O) 2 OO + NO 2 ).…”
Section: Comprehensive Measurements Of S-containing Productssupporting
confidence: 90%
“…[3] Despite there being many laboratory simulations of DMS oxidation, the underlying mechanism remains largely unknown because of the complexity of many reaction channels involving short-lived radical species,a nd al arge discrepancy still exits between the experimental measurements and simulation results. [4] According to the frequently applied kinetic model, the oxidation of DMS in the gas phase occurs through as tepwise formation of radical species CH 3 SO x (x = 0-3). [5] Thef inal radical species,C H 3 SO 3 ,c an either dissociate into CH 3 and SO 3 followed by H 2 SO 4 formation, abstract hydrogen from atmospheric volatile organic compounds R-H to produce MSA, or react with NO 2 to give methylsulfonyl nitrate,C H 3 SO 3 NO 2 .…”
mentioning
confidence: 99%
“…Despite there being many laboratory simulations of DMS oxidation, the underlying mechanism remains largely unknown because of the complexity of many reaction channels involving short‐lived radical species, and a large discrepancy still exits between the experimental measurements and simulation results 4. According to the frequently applied kinetic model, the oxidation of DMS in the gas phase occurs through a stepwise formation of radical species CH 3 SO x ( x =0–3) 5.…”
mentioning
confidence: 99%
“…The unit of the rate constants for the dust sorption reactions is m 3 m -2 s -1 . b The rate constant parameters of SO2 oxidation in gas phase are taken from previous studies as shown in note of each reactions and can be also found in Chen and Jang (2012). T (K) is the temperature.…”
Section: Figure S8mentioning
confidence: 99%